Crystal growth and spectral broadening of a promising Yb:CaLuxGd1−xAlO4 disordered crystal for ultrafast laser application. Issue 12 (3rd March 2017) - Hu, Qiangqiang; Jia, Zhitai; Volpi, Azzurra; Veronesi, Stefano; Tonelli, Mauro; Tao, Xutang
Abstract : This work reports on the growth and spectral broadening of a promising Yb:CaLu x Gd1− x AlO4 disordered crystal for ultrafast laser application. Abstract : Yb:CaLu x Gd1− x AlO4 (Yb:CLGA) crystals have been grown and studied for the first time. A more disordered structure than that of the Yb:CaGdAlO4 (Yb:CGA) crystal was designed by introducing Lu 3+ ions into the crystal. The absorption spectra at 9.6 K provided clear evidence for the disordered structure of the Yb:CLGA crystal. Moreover, further spectral broadening was achieved compared to that of the Yb:CGA crystal. The crystal quality and spectroscopic properties of the Yb:CLGA crystal with the highest degree of disorder were investigated in detail. Improved ultrafast laser oscillators, in terms of narrower pulse width and higher peak power, are expected with this modified crystal.